Evaluating heathland restoration belowground using different quality indices of soil chemical and biological properties - Duddigan, Sarah; Gil-Martínez, Marta; Fraser, Tandra; Green, Iain; Diaz, Anita; Sizmur, Tom; Pawlett, Mark; Raulund-Rasmussen, Karsten; Tibbett, Mark (MDPI, 2020)
Reversion of agricultural land to heathland and acid grassland is a priority for the conservation of these rare habitats. Restoration processes require interventions to reverse the effects of fertilization and acidity amelioration undertaken during decades of agricultural production. Belowground assessments of restoration success are few, and we have examined the utility of soil indices as a rationalized tool for land managers and restoration practitioners to assess the efficacy of restoration practice. To achieve this, we assessed a large number of variables, many of which might be near redundant, that could be optimized for such indices. We used a 14-year field experiment contrasting acidified pasture (treated with elemental sulphur), control (untreated) pasture, and adjacent native heathland and acid grassland sites. Based on biotic and abiotic parameters, several ‘heathland restoration indices’ (resembling soil quality indices) were generated using a minimum dataset identified through principal component analysis and a linear scoring system. For comparison we also conducted alternative analyses of all parameters, using nonmetric multidimensional scaling plots and analyses of similarity (ANOSIM). Use of heathland restoration indices showed that elemental sulphur application had changed the soil chemical conditions, along with the vegetation assemblage, to be comparable to that of native acid grassland, but not the belowground biology. ANOSIM on full datasets confirmed this finding. An index based on key variables, rather than an analysis of all biotic and abiotic parameters, can be valuable to land managers and stakeholders in acid grassland and heathland restoration.
Keywords: Restoration ecology; heathland restoration index; soil biology; heathland; acid grassland; biological indicators